2016
DOI: 10.1038/srep33959
|View full text |Cite
|
Sign up to set email alerts
|

Controllably releasing long-lived quantum memory for photonic polarization qubit into multiple spatially-separate photonic channels

Abstract: We report an experiment in which long-lived quantum memories for photonic polarization qubits (PPQs) are controllably released into any one of multiple spatially-separate channels. The PPQs are implemented with an arbitrarily-polarized coherent signal light pulses at the single-photon level and are stored in cold atoms by means of electromagnetic-induced-transparency scheme. Reading laser pulses propagating along the direction at a small angle relative to quantum axis are applied to release the stored PPQs int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Spatially insensitive filtering is essential for the memory to take advantage of its inherent multimode capability. Commonly used frequency filtering cavities 5 , 11 , 13 transmit only one spatial mode. To overcome this issue, we use two separate optically pumped hot rubidium vapor cells with buffer gas and paraffin coating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatially insensitive filtering is essential for the memory to take advantage of its inherent multimode capability. Commonly used frequency filtering cavities 5 , 11 , 13 transmit only one spatial mode. To overcome this issue, we use two separate optically pumped hot rubidium vapor cells with buffer gas and paraffin coating.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplexing in optical fibers or in free-space is essential in modern techniques for high-throughput transmission 1,2 . Similarly, as quantum technologies mature, the necessity of multiplexing in photon-based quantum communication becomes clear 3 and much effort is devoted to various schemes exploiting spatial [4][5][6][7][8][9][10][11][12] temporal [13][14][15][16][17][18] or spectral 19,20 degrees of freedom. Utilization of many modes can finally allow efficient application of the Duan-Lukin-Cirac-Zoller (DLCZ) protocol 19,[21][22][23][24] and offer nearly-deterministic generation of multi-photon states [25][26][27] later applicable in quantum enhanced sensing technologies 28,29 as well as optical quantum computation 30 .…”
Section: Introductionmentioning
confidence: 99%
“…These relations allow for the possibility of manipulating the emission direction of the signal pulse by changing either wave vector on the right hand side of (15). Using emission control pulses in different directions was proposed in [7,17], but has the disadvantage of transferring the problem of controlling the direction of a light-field from the signal beam to the control beam, i.e. one needs active optical elements or different sources for the control beam.…”
Section: A Phase Matching Conditions and Directionalitymentioning
confidence: 99%
“…Chen et al [6] demonstrated forward and backward retrieval with EIT. In [7], forward retrieval and routing with a small 'array' of possible control beams was achieved. [8] recognized phase matching and the spin-wave vector κ as important for directionality and proposed multi-mode storage by having an array of control fields with sufficiently differing angles that any control beam only affects its own spin wave.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach to high-dimensionality was demonstrated by coupling a memory for photonic polarization qubits to spatially separated output channels into multiple spatiallyseparate photonic channels. 167 Recent experiments are pushing the number of accessible spin wave modes. The simultaneous storage of up to 60 independent atomic spinwave modes in Rb vapour 168 and 665 spin-wave modes in a cold atomic ensemble have been demonstrated with a Raman memory, 168 encoding modes determined by the photonic wavevector.…”
Section: Electromagnetically Induced Transparency and Memoriesmentioning
confidence: 99%